Niger : First Review Under the Extended Credit Facility Arrangement and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report, 2022)
Since program approval, Niger has been facing a more challenging international context, including the fall-out from the war in Ukraine, which is exacerbating pressures on food and fertilizer prices. Moreover, unfavorable rainfall and a deterioration in the security situation led to a deceleration of growth to 1.3 percent in 2021 and an acute food crisis. A temporary deviation of fiscal deficit targets from the program in 2022-23 is needed to respond to urgent expenditure pressures, while the medium-term outlook is largely unchanged favored by the start of oil exports through the new pipeline.